Media Interactive Board Game Berbasis Phenomenon Based Learning Untuk Mengatasi Learning Loss Siswa Kelas IV Sekolah Dasar - I Dewa Ayu Nyoman Artanti, I Dewa Ayu Nyoman Artanti; I Wayan Widiana; Tegeh, I Made (Jurnal Media dan Teknologi Pendidikan, 2023)
The Covid-19 pandemic has impacted the education sector in Indonesia. During the pandemic, education, especially the teaching and learning process, was shifted to online mode or distance learning. However, this transition forces all components of education to switch to digital learning without any preparation and maturity both physically, mentally, and financially. The impact is that there is no equal distribution of learning received by students, resulting in the phenomenon of learning loss. Learning loss has an impact on the activity, psychological, and intellectual of students to date. The purpose of this research is to produce learning media based on Phenomenon Based Learning that can overcome the problem of learning loss in grade IV elementary school students. The development model in this research is ADDIE (Analyze, Design, Development, Implementation, Evaluation) with research subjects namely experts, practitioners or teachers, and students. The data collection techniques used were questionnaires and tests. The results of this study are validity analysis, practicality, and effectiveness of Interactive Board Game media.